2015
DOI: 10.1287/orsc.2015.0972
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Personality and Social Networks: A Meta-Analysis of Personality, Network Position, and Work Outcomes in Organizations

Abstract: U sing data from 138 independent samples, we meta-analytically examined three research questions concerning the roles of personality and network position in organizations. First, how do different personality characteristics-selfmonitoring and the Big Five personality traits-relate to indegree centrality and brokerage, the two most studied structurally advantageous positions in organizational networks? Second, how do indegree centrality and brokerage compare in explaining job performance and career success? Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
279
4
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 345 publications
(314 citation statements)
references
References 97 publications
9
279
4
2
Order By: Relevance
“…Results have indicated that instructional leadership affects Transformational leadership, emotional intelligence, job satisfaction, decision making strategy, school environment, organizational commitment and organizational citizenship at medium level. This finding shows parallelism with other meta-analysis findings which examine the relations between instructional leadership and some organizational variables (Fang et al, 2015;Jackson, Meyer, & Wang, 2013;Karadağ, 2015;Karadağ, Çiftçi, & Bektaş, 2015;Tian, Risku, & Collin, 2015). This finding means that with the exhibition of instructional leadership behavior, teachers adopt positive attitudes for their work, love their work, they feel themselves belong in their school and association at school environment is at high level (Locke, 1976;Luthans, 1992;Wray, Luft, & Highland, 1996).…”
Section: Discussionsupporting
confidence: 80%
“…Results have indicated that instructional leadership affects Transformational leadership, emotional intelligence, job satisfaction, decision making strategy, school environment, organizational commitment and organizational citizenship at medium level. This finding shows parallelism with other meta-analysis findings which examine the relations between instructional leadership and some organizational variables (Fang et al, 2015;Jackson, Meyer, & Wang, 2013;Karadağ, 2015;Karadağ, Çiftçi, & Bektaş, 2015;Tian, Risku, & Collin, 2015). This finding means that with the exhibition of instructional leadership behavior, teachers adopt positive attitudes for their work, love their work, they feel themselves belong in their school and association at school environment is at high level (Locke, 1976;Luthans, 1992;Wray, Luft, & Highland, 1996).…”
Section: Discussionsupporting
confidence: 80%
“…Who comes to occupy these central network positions? Recent research suggests that individuals' personalities influence their ability to attract social ties (6)(7)(8)(9)(10)(11),* but this personality-centrality relationship may vary depending on the type of connection that one uses to define a network. For example, extraverts become more central than introverts in networks defined by friendship (6).…”
mentioning
confidence: 99%
“…As a result, only high PsyCap-EI members need be sensitive to the liked perception, since they can undertake deliberate repair of relationships [109]. Due to this, and the ability to connect with socially desirable conspecifics, high PsyCap-EI members will experience more intense BPN-relatedness [110].…”
Section: Psycap-ei → Liked → Bpn-relatednessmentioning
confidence: 99%